2022
DOI: 10.1007/s10880-022-09859-8
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration into Experiences and Attitudes Regarding Psychosocial Challenges, Self-compassion, and Mindfulness in a Population of Adults with Cystic Fibrosis

Abstract: To investigate the current psychosocial challenges faced by adults with Cystic Fibrosis (CF), while exploring attitudes and experiences of mindfulness and self-compassion. Mindfulness and self-compassion are important resources for supporting psychological and physical well-being, yet there is limited research exploring these positive psychology concepts in CF literature. Twenty UK domiciled adults with a diagnosis of CF, took part in a semi-structured interview. Using a thematic analysis approach, four themes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…This is consistent with a previous review reporting that decreased physical and mental aspects of health correlated with decreased “social functioning” scores and that social support was an important aspect of CF adult life [ 48 ]. Identifying a negative social perception can help to propose personalized interventions [ 5 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a previous review reporting that decreased physical and mental aspects of health correlated with decreased “social functioning” scores and that social support was an important aspect of CF adult life [ 48 ]. Identifying a negative social perception can help to propose personalized interventions [ 5 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data suggested that individuals with CF proactively engage with a variety of mindfulness practices, including both formal and informal methods, often as a means of coping with the complexities of life with CF, and with the hope of achieving better health and wellbeing. During an era of CFTR modulator therapies where disease characteristics are changing, adults with CF are currently experiencing an increased emotional burden of not only living with a reduced life expectancy, but also exceeding the CF life expectancy, as highlighted in this study and recent prior research (Kauser et al, 2022;Keyte et al, 2022). With the understanding that this will most likely become a shared reality for many adults with CF, an increased need for additional psychological support and education is required for the growing population of older patients with CF.…”
Section: Discussionmentioning
confidence: 72%
“…The distress and psychological burden caused by CF complexities have detrimental effects on emotional wellbeing and can further impact on other areas of life such as ones' motivation to comply with treatment adherence (Kauser et al, 2022). Notwithstanding, the use of mindfulness has been proposed as an important resource for supporting physical and psychological wellbeing in the adult CF population , recognising the developments of mindful eating .…”
mentioning
confidence: 99%